Rapproachement Model for Economic Integration - Chun, Hong Tack (Economic Systems in South and North Korea : The Agenda for Economic Integration, 1995)
Propelled by the dissolution of the Soviet Union, the pace of change in the world has become more rapid in the final decade of the twentieth century than at any time in history. The economies of almost all former socialist countries have undergone a transformation and have shifted in the direction of the market system. Although North Korea remains an exception to this worldwide trend, the change in the international order not only presents South Korea with an opportunity to normalize its relationship with North korea but also opens the way to the eventual reunification of the Korea peninsula. As the German experience demonstrates, unification entails both material and social costs. The benefits of unification appear to outweigh the costs, however, particularly if the cost can be spreadout over time through a gradual approach. For such and approach to be a viable option, North Korea would have to change, and indeed it is expected to change, because its economic development under the iuche(self-reliance) model has come to a standstill, The two Korea societies have been organized according to entirely different principles for half a century, and to narrow the divergence South Korea likewise must change. Relatively little attention, however, has been paid to the transition period through which the two economies would have to pass before eventual unification. This book helps to fill this important gap in the research. The authors provide a detailed comparison of the South and North Korean economic systems, identify transition period issues, and propose reforms in the respective sectors of the two economies. This book is therefore useful not only for providing a clear picture of the status quo in the South and North Korean economies but also for explaining the policy implications of a transition period that could begin at any time. The conclusions and policy recommendations represent the views of the authors and not necessarily those of the Korea Development Institute. The Korea Development Institute and the East-West Center in the Honolulu, Hawaii, hosted a conference at the Center from August 2 to August 13, 1993, on "Economic Systems in South and North Korea and a Proposal for Economic Integration." The chapters of this book were developed form papers presented at that conference. (※ 서문에서 발췌한 내용임)